Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.3177/jnsv.53.253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monascus-Fermented Products on Learning and Memory in the SAMP8 Mice

Abstract: SummaryThe purpose of this study was to evaluate the impact of Monascus -fermented products (MP) as regards certain changes in behavior for SAMP8 mice. Both male and female SAMP8 mice were fed a 0.03% MP diet from 3 mo of age to 11 mo of age. The results indicated that the grading score of passive avoidance behavior was significantly lower in the MP diet groups than in the control diet groups in both male and female SAMP8 mice ( p Ͻ 0.05). The MP diet-augmented test-animal body weight, feed intake and feed eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Monacolin K (also known as lovastatin) is one of the main monacolins that has been found to have various pharmacological activities, including lowering blood cholesterol levels and reducing oxidative damage. Several in vivo studies have indicated that Monacolins K can permeate the blood-brain barrier (38,39). In addition to monacolins, considerable amounts of gamma-aminobutyric acid (GABA) have also been found in RMR, which is the main inhibitory neurotransmitter in the central nervous system (5).…”
Section: The Effects Of Fermented Foods On Cognitive Functionmentioning
confidence: 99%
“…Monacolin K (also known as lovastatin) is one of the main monacolins that has been found to have various pharmacological activities, including lowering blood cholesterol levels and reducing oxidative damage. Several in vivo studies have indicated that Monacolins K can permeate the blood-brain barrier (38,39). In addition to monacolins, considerable amounts of gamma-aminobutyric acid (GABA) have also been found in RMR, which is the main inhibitory neurotransmitter in the central nervous system (5).…”
Section: The Effects Of Fermented Foods On Cognitive Functionmentioning
confidence: 99%
“…When the learning ability of mice is measured by an avoidance test using a shuttle box setup, passive or active avoidance methods are often used (26)(27)(28). In both avoidance methods, the mouse is first given an electric shock in the dark compartment.…”
Section: Discussionmentioning
confidence: 99%